Development of a gimbal-swing irradiation technique for uniform expanded-field, wedged-beam, and intensity-modulated radiation therapy. (30th November 2016) - Ono, Tomohiro; Miyabe, Yuki; Yokota, Kenji; Takahashi, Kunio; Akimoto, Mami; Mukumoto, Nobutaka; Ishihara, Yoshitomo; Nakamura, Mitsuhiro; Mizowaki, Takashi; Hiraoka, Masahiro
Abstract: The purpose of this study was to develop a new irradiation technique for a uniform expanded irradiation field (uniform expanded-field), wedged-beam, and intensity-modulated radiation therapy (IMRT) using the gimbaled x-ray head swing (gimbal-swing) of Vero4DRT. The gimbal has two orthogonal axes which provides tilt and pan movements. The Vero4DRT has a maximum field size of 150 × 150 mm 2 . By swinging the gimbaled x-ray head ±35 mm at the isocenter level, the field size was expanded from 150 to 220 mm in the tilt motion. In order to obtain a uniform dose distribution, continuous irradiation was delivered through a parallelogram-shaped radiation field by the gimbal-swing. Dosimetric characteristics of the uniform expanded-field were evaluated using irradiated film. In order to obtain a wedge-beam, continuous irradiation was delivered through a triangular-shaped radiation field by the gimbal-swing. Three different wedge angles: 15°, 30°, and 45°, were measured on the irradiated film and compared with the theoretical wedge angles. Additionally, the gimbal-swing irradiation technique was applied to IMRT for three clinical cases. The absolute point dose and relative dose distributions were evaluated. In the uniform field, the field size, penumbra, flatness, and symmetry were 220.1 mm, 6.3–6.4 mm, 3.2%, and −0.4% for the tilt motion. The differences between measured and theoretical wedge angles were within 0.2°. The absolute dose difference of the gimbal-swing IMRT field between the measured dose with an ion chamber and the calculated dose was within 2.3% for three cases. The passing rate of 3%/3 mm gamma analysis was larger than 93.7%. A new technique for gimbal-swing irradiation was developed. To extend the clinical application of the Vero4DRT for targets with a size over 150 × 150 mm 2, the uniform expanded-field, wedged-beam, and gimbal-swing IMRT would be effective.